Ageing, arteriosclerosis, dizziness and Baryta carb - Ghosh, A. (British Homeopathic Journal, 1979)
Twelve patients with arteriosclerosis and dizziness are discussed. Because baryta poisoning causes arteriosclerosis the same remedy was used to treat these patients; twice-daily doses of Baryta carb. 6x or 30c for six months were found to be effective.